Distinctive Gut Microbiota Alteration Is Associated with Poststroke Functional Recovery: Results from a Prospective Cohort Study - Yini Dang; Xintong Zhang; Yu Zheng; Binbin Yu; Dijia Pan; Xiaomin Jiang; Chengjie Yan; Qiuyu Yu; Xiao Lu (Neural Plasticity)
Objectives. Functional prognosis is potentially correlated with gut microbiota alterations following the dysregulation of the gut-microbiota-brain axis after stroke. This study was designed to explore the poststroke alterations of gut microbiota and potential correlations between gut microbiota and global functions. Methods. A total of thirty-eight patients with stroke and thirty-five healthy demographics-matched controls were recruited. Their fecal DNAs were extracted, and the V3-V4 regions of the conserved bacterial 16S RNA were amplified and sequenced on the Illumina MiSeq platform. Microbial composition, diversity indices, and species cooccurrence were compared between groups. Random forest and receiver operating characteristic analysis were used to identify potential diagnostic biomarkers. Relationships between discriminant bacteria and poststroke functional outcomes were estimated. Results. Higher alpha diversity of gut microbiota was observed in poststroke patients as compared to the healthy controls (p<0.05). Beta diversity showed that microbiota composition in the poststroke group was significantly different from that in the control group. Relative abundance of nine genera increased significantly in poststroke patients, while 82 genera significantly decreased (p<0.05). The accuracy, specificity, and susceptibility of the optimal model consisted of the top 10 discriminant species were 93%, 100%, and 86%, respectively. Subgroup analysis showed that bacterial taxa abundant between subacute and chronic stroke patients were overall different (p<0.05). The modified Rankin scale (mRS) (r=−0.370, p<0.05), Fugl-Meyer assessment (FMA) score (r=0.364, p<0.05), water swallow test (WST) (r=0.340, p<0.05), and Barthel index (BI) (r=0.349, p<0.05) were significantly associated with alterations of distinctive gut microbiota. Conclusions. The gut microbiota in patients with stroke was significantly changed in terms of richness and composition. Significant associations were detected between alterations of distinctive gut microbiota and global functional prognosis. It would facilitate novel treatment target selection in the context of stroke while the causal relationships between distinctive gut microbiota alterations and functional variations need to be further verified with well-designed studies.